Selected Decisions Supplement (13th Ed). (Selected Decisions; Issue, Year, 1988)
This paper analyses several IMF's selected decisions of the Executive Board and selected documents. This volume is the Thirteenth Issue of Selected Decisions of the IMF and Selected Documents. It contains the decisions, interpretations, and resolutions of the Executive Board and the Board of Governors of the IMF, and related documents, to which frequent reference is made in the current activities of the IMF. Moreover, the volume contains certain documents relating to the IMF and the United Nations. With few exceptions, the decisions are of a general nature and relate to certain obligations, policies, and procedures under the Articles of Agreement. This issue contains most of the decisions published in the Twelfth Issue that remain in effect, as well as new general decisions adopted after the publication of the Twelfth Issue. Decisions of the IMF that are incorporated in the Rules and Regulations are not reproduced in this volume.